Counsellors’ experiences of integrating virtual interventions to provide mental health support for students - Gregory Mitchell; Dalray Gradidge; Nomalungelo Ntlokwana (Journal of Student Affairs in Africa)
This study sought to explore the experiences of counsellors at Nelson Mandela University's Emthonjeni Student Wellness counselling unit regarding the implementation of a blended counselling model, integrating virtual interventions into the existing practice model. Grounded theory methodology was employed to generate an understand of the evolving counselling practices and the growing acceptance of this model in a student counselling centre at a South African public university. This requires integration of psychological knowledge and experience with other domains, such as information technology, professional ethics, and higher education student support. Data were collected through semi-structured interviews with counsellors working within the university’s counselling unit. The emergent theoretical framework shed light on the evolution of counselling practices within the university context and how students’ mental health and wellness can be supported using virtual interventions. The main themes identified in the findings included: (i) the necessary transition to integration, (ii) challenges and obstacles, (iii) benefits and advantages (iv) diversity and uniqueness, and (v) training points for counsellors. Key concepts that can form the basis of a blended counselling model and the necessary training and development of counsellors in such a model, include (i) adaptation and flexibility, (ii) technological proficiency, (iii) cultural sensitivity and diversity, and (iv) boundary management. Each of these key concepts relate to areas for skill development in counsellors and would benefit from an integrative, evidence- and scholarship-based approach to benefit student counselling services within South African public universities.